Morphology Control of TiO2 Nanorods Using KBr Salt for Enhancing the Photocatalytic Activity of TiO2 and MoS2/TiO2 Heterostructures - Zeineb A. Thiehmed (15945042) (2022)
In this study, the effect of KBr salt on the growth of TiO2 nanorods (NRs) was systematically studied. The addition of KBr with different concentrations provides a controllable growth of TiO2 NRs using hydrothermal method. The results revealed that the presence of KBr molecules affects the growth rate by suppressing the growth in the lateral direction and allowing for axial growth. This results in affecting the morphology by decreasing the diameter of the nanorods, and increasing the free space between them. Enhancing the free spaces between the adjacent nanorods gives rise to remarkable increase in the internal surface area, with more exposure side surface. To obtain benefit from the enlargement in the inner surface area, TiO2 NRs were used for the preparation of MoS2/TiO2 heterostructures. To study the influence of the morphology on their activity, TiO2 NRs samples with different KBr concentrations as well as the MoS2/TiO2 heterostructures were evaluated towards the photocatalytic degradation of Rhodamine B dyes.  Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/nano12172904